Fasting plasma total IGF-1 and bile acids levels correlate with the disease prognostic indices in type 2 diabetic patients: IGF-1 and bile acids in type 2 diabetes (African Journal of Biomedical Research, 2021)
Although they are pathophysiologically involved, evidences inconsistently highlight a relationship between type 2 diabetes mellitus (T2DM) and its prognosis with variation in circulating levels of each of bile acids (BAs) and Insulin-like growth factor-1 (IGF-1). We aimed to investigate the possible role of BAs and IGF-1 in the prediction of T2DM and its complications in Saudi patients. Their fasting plasma levels were correlated to each other and to the disease clinical and biochemical prognostic indices. This is an analytical cross-sectional Tertiary care center-based study. We consecutively included 184 hospital-diagnosed T2DM patients and 113 healthy controls from their accompanying relatives. Anthropometrics, demographics and disease history were recorded. Fasting plasma Levels of total BAs, lipids and glucose were assayed colorimetrically, and, total IGF-1, hemoglobin A1c (HbA1c), insulin, and C-reactive protein (CRP) were assayed. Atherogenic index of plasma (AIP) and homeostatic model assessment of insulin resistance (HOMA-IR) were calculated. Diabetic patients were stratified by disease severity score and treatment score for association analysis. Correlations among parameters were assessed. Area under the receiver operating characteristic (ROC) curve (AUC) assessed the discriminative power of BAs and IGF-1 vs. prognostic indices.  Our main outcomes were correlation among BAs and IGF-1 with diabetes prognostic indices. Majority of patients were overweight, females,
Keywords: Type 2 diabetes mellitus, bile acids, insulin-like growth factor-1, complications, disease duration, glycemic control, prognostic indices